A systematic review of the co-occurrence of self-harm and aggression: Is dual harm a unique behavioural construct? - Shafti, Matina; Taylor, Peter; Forrester, Andrew; Handerer, Fritz; Pratt, Daniel (Frontiers in Psychiatry, 2023)
Dual harm is the co-occurrence of self-harm and aggression during an individual’s lifetime. It is unclear whether sufficient evidence exists for dual harm as a unique clinical entity. This systematic review aimed to examine whether there are psychological factors that are uniquely associated with dual harm when compared to those who have engaged in sole harm (self-harm alone, aggression alone) and no harmful behaviours. Our secondary aim was to conduct a critical appraisal of the literature. The review searched PsycINFO, PubMed, CINAHL, and EThOS on 27/09/2022, resulting in 31 eligible papers that represented 15,094 individuals. An adapted version of the Agency for Healthcare Research and Quality was used to assess risk of bias and a narrative synthesis was conducted. The included studies assessed differences in mental health problems, personality and emotion related factors between the different behavioural groups. We found weak evidence that dual harm is an independent construct with unique psychological characteristics. Rather, our review suggests that dual harm results from the interaction of psychological risk factors that are separately associated with self-harm and aggression. The critical appraisal identified numerous limitations within the dual harm literature. Clinical implications and recommendations for future research are provided.